Frequency, distribution, and molecular recognition of Argas persicus (Argasidae) infestation of local chicken Gallus gallus domesticus in Mosul city - Abeer A. Ahmed; Layan Y. Khalil (Iraqi Journal of Veterinary Sciences)
Seven hundred sixty-four ticks of Argas persicus have been collected from 390 local chickens at four locations in Mosul city. Ticks have been determined by investigating their existence in different chicken cages. The raised distribution rates through the shelters in the wooden cage reached 61.9%, no presence of ticks appeared in the iron cage 0% as well as the total infestation rate with A. persicus in the shelter was 36.47%. The highest shelter infestation rate was from the eastern areas of the city 11.76%, although the lowest ratio was for those areas located in the west 6.47%. Moreover, the study showed statistical differences in frequency rates between summer 22.2% and autumn 10%. Tick frequency rates through July were elevated 33.4%, matching those for other summer and fall months 20.8, 29.7, 12.4, and 3.7%. A significant difference also could be seen in adult females’ numbers and rates among the disparate months 25.3, 31.6, 34.5, 6.3, and 2.3%. The same applies regarding the nymphs and larvae of A. persicus, with significant differences by month in which the study was conducted for ticks’ males; no noticeable differences have been shown among months of this work. Molecular analysis for 32 specimens of singular ticks was accustomed for extraction of DNA and restrained to PCR utilizing definite primers for exaggeration of sectional fragment of COX1, as well as 16SrRNA genes. All 32 isolates showed effective PCR results following gel electrophoresis with 240 bp and 606 bp product sizes.